Structural features of the Myanmar economy through the lens of a 2017 Social Accounting Matrix - Dirk van Seventer; Finn Tarp; Khin Ohnmar Myint Thein; Soe Thie Nu Htwe; Nyaung Tai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Based on a recently constructed 2017 Social Accounting Matrix, we examine structural aspects of the Myanmar economy. The exposition ranges from industry, trade, household income, and expenditure to labour market issues. Agriculture remains dominant, accounting for about 50 per cent of employment although its contribution to gross domestic product is about 17 per cent. Services, both public and private, represent 55 per cent of gross domestic product and 33 per cent of employment. Manufacturing plays a minor role, at 17 per cent of gross domestic product and less than ten per cent of employment. More than 60 per cent of household income is earned in rural areas. Simple multiplier calculations show low economic integration. Some surprising results can be explained by lack of data integration and consolidation, pointing to the need for further data gathering and Social Accounting Matrix construction.
Keywords: D31; D57; E16; J21; 330; Balance of Payment; income distribution; Labour Force Survey; National Accounts; Social Accounting Matrix; Supply and Use Table